2016
DOI: 10.1002/jcc.24494
|View full text |Cite
|
Sign up to set email alerts
|

Variation of free-energy landscape of the p53 C-terminal domain induced by acetylation: Enhanced conformational sampling

Abstract: The C‐terminal domain (CTD) of tumor suppressor protein p53 is an intrinsically disordered region that binds to various partner proteins, where lysine of CTD is acetylated/nonacetylated and histidine neutralized/non‐neutralized. Because of the flexibility of the unbound CTD, a free‐energy landscape (FEL) is a useful quantity for determining its statistical properties. We conducted enhanced conformational sampling of CTD in the unbound state via virtual system coupled multicanonical molecular dynamics, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…A high degree of helicity in the unbound p53-CTD was described in a recently published computational work. 60 Such strong conformational propensity is inconsistent with circular dichroism data 24,60 and could be due not only to force field limitations, but also to the choice of starting structures derived from the S100B(bb) bound conformation. 60 In 30.7% of the helical structures, the residual helicity spans the 381 KKL 383 stretch.…”
Section: Stability Of the S100b(bb)-bound Conformation In Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high degree of helicity in the unbound p53-CTD was described in a recently published computational work. 60 Such strong conformational propensity is inconsistent with circular dichroism data 24,60 and could be due not only to force field limitations, but also to the choice of starting structures derived from the S100B(bb) bound conformation. 60 In 30.7% of the helical structures, the residual helicity spans the 381 KKL 383 stretch.…”
Section: Stability Of the S100b(bb)-bound Conformation In Solutionmentioning
confidence: 99%
“…60 Such strong conformational propensity is inconsistent with circular dichroism data 24,60 and could be due not only to force field limitations, but also to the choice of starting structures derived from the S100B(bb) bound conformation. 60 In 30.7% of the helical structures, the residual helicity spans the 381 KKL 383 stretch. In all other cases, single helical turns are observed in the disordered, and unbound N-terminal tail, often in addition to the helical turn at 381 KKL 383 .…”
Section: Stability Of the S100b(bb)-bound Conformation In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ikebe et al reported that the larger the value of ω becomes, the smaller the helical propensity in the resultant conformational ensemble at 300 K . Iida et al set ω=0.80 to investigate a free‐energy landscape of the C‐terminal domain of p53, which is an intrinsically disordered segment . We also set ω=0.80 for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…In the sampling, we introduced a virtual variable that has a role in confining the conformation in the zone: i.e., the molecular system (real system) interacts with a “virtual system,” which is an abstract and unrealistic system defined by the virtual variable . This technique, named V‐McMD, was combined with McMD . Similarly, the virtual system was combined with AUS and was designated as a virtual‐system coupled AUS (V‐AUS) .…”
Section: Introductionmentioning
confidence: 99%